Undang-Undang Republik Indonesia Nomor 32 Tahun 2009 Sebagai Pedoman Perlindungan Lingkungan Dalam Upaya Perlindungan Bali Berkelanjutan - I Nyoman Suadnyana (PARIKSA: Jurnal Hukum Agama Hindu, 2021)
Law of the Republic of Indonesia Number 32 of 2009 is a set of rules regarding environmental protection and management. It is very important that rules are formed, understood, obeyed and implemented in everyday life. The goal is to guide the protection of the environment. Environmental Law was formed to protect the environment. The Law of the Republic of Indonesia Number 32 of 2009 provides strong regulations regarding planning, utilization, control, maintenance, supervision and law enforcement of the environment. Protection of the environment is important to protect the environment, both traditions, customs and cultures that have been passed down. Law of the Republic of Indonesia Number 32 of 2009 is used as a guideline for environmental protection in an effort to protect Bali sustainably so that it is environmentally friendly through the implementation of Tri Hita Karana, both parhyangan, pawongan, and palemahan.